TREATMENT OF AMERICAN TEGUMENTARY LEISHMANIOSIS WITH FLUCONAZOLE: CASE REPORT - Xavier, Kauane Mayra de Oliveira; Puster, Rainardo Antônio; Batista, Hermes Melo Teixeira; Rodrigues, Jorge Luiz Nobre (Amadeus International Multidisciplinary Journal, 2020)
Abstract: Leishmaniasis are diseases caused by protozoan parasites of the Leishmania genus, seen as a major public and social health problem, they represent a complex of diseases with different clinical presentations. Pentavalent antimonial drugs are the first choice in their treatment, however, this medications have disadvantages, such as the application and risks attributed to the toxicity. In this context, therapeutic options that present a suitable intake and satisfactory results are studied. The authors present a clinical case of American cutaneous leishmaniasis in a male patient, 89 years old, with cutaneous lesions on the nasal dorsum and on the left infraorbital margin, after the diagnosis, therapy with oral fluconazole was started, thus improving the disease. Oral triazole antifungals are a controversial topic in cutaneous leishmaniasis, even so, the use of oral fluconazole can be considered in patients with skin lesions, especially in patients susceptible to the greater possibility of complications due to side effects of pentavalent antimonial drugs. Keywords: American Cutaneous Leishmaniasis. Fluconazole. Public health.